5.9.30 Problems 2901 to 3000

Table 5.687: First order ode linear in derivative

#

ODE

Mathematica

Maple

6904

\[ {}x y^{\prime }-2 y = 0 \]

6905

\[ {}y^{\prime } = -\frac {x}{y} \]

6906

\[ {}y^{\prime }+2 y = 0 \]

6907

\[ {}5 y^{\prime } = 2 y \]

6914

\[ {}3 x y^{\prime }+5 y = 10 \]

6915

\[ {}y^{\prime } = y^{2}+2 y-3 \]

6916

\[ {}\left (y-1\right ) y^{\prime } = 1 \]

6920

\[ {}y y^{\prime }+\sqrt {16-y^{2}} = 0 \]

6924

\[ {}y^{\prime } = \sqrt {1-y^{2}} \]

6926

\[ {}y^{\prime } = f \left (x \right ) \]

6929

\[ {}y^{\prime } = 5-y \]

6930

\[ {}y^{\prime } = 4+y^{2} \]

6933

\[ {}y^{\prime } = y-y^{2} \]

6934

\[ {}y^{\prime } = y-y^{2} \]

6935

\[ {}y^{\prime }+2 x y^{2} = 0 \]

6936

\[ {}y^{\prime }+2 x y^{2} = 0 \]

6937

\[ {}y^{\prime }+2 x y^{2} = 0 \]

6938

\[ {}y^{\prime }+2 x y^{2} = 0 \]

6947

\[ {}y^{\prime } = 3 y^{{2}/{3}} \]

6948

\[ {}x y^{\prime } = 2 y \]

6949

\[ {}y^{\prime } = y^{{2}/{3}} \]

6950

\[ {}y^{\prime } = \sqrt {x y} \]

6951

\[ {}x y^{\prime } = y \]

6952

\[ {}y^{\prime }-y = x \]

6953

\[ {}\left (4-y^{2}\right ) y^{\prime } = x^{2} \]

6954

\[ {}\left (y^{3}+1\right ) y^{\prime } = x^{2} \]

6955

\[ {}\left (x^{2}+y^{2}\right ) y^{\prime } = y^{2} \]

6956

\[ {}\left (y-x \right ) y^{\prime } = x +y \]

6957

\[ {}y^{\prime } = \sqrt {y^{2}-9} \]

6958

\[ {}y^{\prime } = \sqrt {y^{2}-9} \]

6959

\[ {}y^{\prime } = \sqrt {y^{2}-9} \]

6960

\[ {}y^{\prime } = \sqrt {y^{2}-9} \]

6961

\[ {}x y^{\prime } = y \]

6962

\[ {}y^{\prime } = 1+y^{2} \]

6963

\[ {}y^{\prime } = y^{2} \]

6964

\[ {}y^{\prime } = y^{2} \]

6965

\[ {}y^{\prime } = y^{2} \]

6966

\[ {}y^{\prime } = y^{2} \]

6967

\[ {}y^{\prime } = y^{2} \]

6968

\[ {}y y^{\prime } = 3 x \]

6969

\[ {}y y^{\prime } = 3 x \]

6970

\[ {}y y^{\prime } = 3 x \]

6977

\[ {}y^{\prime } = x -2 y \]

6978

\[ {}y^{\prime } = x^{2}+y^{2} \]

6980

\[ {}y^{\prime }+2 y = 3 x -6 \]

6981

\[ {}y^{\prime } = x \sqrt {y} \]

6982

\[ {}x y^{\prime } = 2 x \]

6983

\[ {}y^{\prime } = 2 \]

6984

\[ {}y^{\prime } = 2 y-4 \]

6985

\[ {}x y^{\prime } = y \]

6989

\[ {}y^{\prime } = y \left (-3+y\right ) \]

6990

\[ {}3 x y^{\prime }-2 y = 0 \]

6991

\[ {}\left (2 y-2\right ) y^{\prime } = 2 x -1 \]

6992

\[ {}x y^{\prime }+y = 2 x \]

6993

\[ {}y^{\prime } = x^{2}+y^{2} \]

6995

\[ {}y^{\prime } = 6 \sqrt {y}+5 x^{3} \]

7000

\[ {}y^{\prime }+y \sin \left (x \right ) = x \]

7001

\[ {}y^{\prime }-2 x y = {\mathrm e}^{x} \]

7004

\[ {}x y^{\prime }+y = \frac {1}{y^{2}} \]

7007

\[ {}\left (1-x y\right ) y^{\prime } = y^{2} \]

7009

\[ {}y^{\prime }+2 y = 3 x \]

7014

\[ {}y^{\prime } = x^{2}-y^{2} \]

7015

\[ {}y^{\prime } = x^{2}-y^{2} \]

7016

\[ {}y^{\prime } = x^{2}-y^{2} \]

7017

\[ {}y^{\prime } = x^{2}-y^{2} \]

7018

\[ {}y^{\prime } = {\mathrm e}^{-\frac {x y^{2}}{100}} \]

7019

\[ {}y^{\prime } = {\mathrm e}^{-\frac {x y^{2}}{100}} \]

7020

\[ {}y^{\prime } = {\mathrm e}^{-\frac {x y^{2}}{100}} \]

7021

\[ {}y^{\prime } = {\mathrm e}^{-\frac {x y^{2}}{100}} \]

7022

\[ {}y^{\prime } = 1-x y \]

7023

\[ {}y^{\prime } = 1-x y \]

7024

\[ {}y^{\prime } = 1-x y \]

7025

\[ {}y^{\prime } = 1-x y \]

7026

\[ {}y^{\prime } = \sin \left (x \right ) \cos \left (y\right ) \]

7027

\[ {}y^{\prime } = \sin \left (x \right ) \cos \left (y\right ) \]

7028

\[ {}y^{\prime } = \sin \left (x \right ) \cos \left (y\right ) \]

7029

\[ {}y^{\prime } = \sin \left (x \right ) \cos \left (y\right ) \]

7030

\[ {}y^{\prime } = x \]

7031

\[ {}y^{\prime } = x \]

7032

\[ {}y^{\prime } = x +y \]

7033

\[ {}y^{\prime } = x +y \]

7034

\[ {}y y^{\prime } = -x \]

7035

\[ {}y y^{\prime } = -x \]

7036

\[ {}y^{\prime } = \frac {1}{y} \]

7037

\[ {}y^{\prime } = \frac {1}{y} \]

7038

\[ {}y^{\prime } = \frac {x^{2}}{5}+y \]

7039

\[ {}y^{\prime } = \frac {x^{2}}{5}+y \]

7040

\[ {}y^{\prime } = x \,{\mathrm e}^{y} \]

7041

\[ {}y^{\prime } = x \,{\mathrm e}^{y} \]

7042

\[ {}y^{\prime } = y-\cos \left (\frac {\pi x}{2}\right ) \]

7043

\[ {}y^{\prime } = y-\cos \left (\frac {\pi x}{2}\right ) \]

7044

\[ {}y^{\prime } = 1-\frac {y}{x} \]

7045

\[ {}y^{\prime } = 1-\frac {y}{x} \]

7046

\[ {}y^{\prime } = x +y \]

7047

\[ {}y^{\prime } = x^{2}+y^{2} \]

7048

\[ {}y^{\prime } = x \left (y-4\right )^{2}-2 \]

7049

\[ {}y^{\prime } = x^{2}-2 y \]

7050

\[ {}y^{\prime } = y-y^{3} \]

7051

\[ {}y^{\prime } = y^{2}-y^{4} \]

7052

\[ {}y^{\prime } = y^{2}-3 y \]